21st Annual BACUS Symposium on Photomask Technology 2002
DOI: 10.1117/12.458301
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and characterization of a DUV raster-scanned mask pattern generation system

Abstract: Etec Systems, Inc., an Applied Materials company, has completed the implementation and characterization of a deep ultraviolet (DUV), multibeam, raster-scanned mask patterning and integrated process solution. The ALTA Ò 4000 mask pattern generation system integrates a new data path, environmental control system, DUV optics, a 257nm DUV continuous-wave laser source, and an environmentally stable chemically amplified resist (CAR) process to deliver superior productivity, improved resolution, and critical dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…smaller is better). 1 Bohan, et al, reported a value of 1.9nm/% dose at isofocal for DX1100 with Aquatar. This provides a principle benchmark against which alternate CAR candidates may be measured.…”
Section: New Car Candidates -Resist Screening Processmentioning
confidence: 97%
“…smaller is better). 1 Bohan, et al, reported a value of 1.9nm/% dose at isofocal for DX1100 with Aquatar. This provides a principle benchmark against which alternate CAR candidates may be measured.…”
Section: New Car Candidates -Resist Screening Processmentioning
confidence: 97%